Contrastive Linguistics - Ke, Ping (Peking University Linguistics Research, 2019)
This book serves as an introduction to contrastive linguistics - the synchronic study of two or more languages, with the aim of discovering their differences and similarities, especially the former, and applying these discoveries to related areas of language study and practice. It discusses the principles and methods, and contrasts English, Chinese, German, and other languages at phonological, lexical, grammatical, textual, and pragmatic levels, focusing more on the useful insights contrastive analysis provides into real-world problems in fields such as applied linguistics, translation and translation studies, English or Chinese as a foreign language, and communication than on the discipline itself.